PENGARUH BLOG, YOUTUBE, DAN FACEBOOK TERHADAP PEMAHAMAN POKOK AJARAN HINDU MAHASISWA STAH NEGERI GDE PUDJA MATARAM - Putu Ari Satya Laksana; I Wayan Ardhi Wirawan; Susilo Edi Purwanto (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
The purpose of this study is to determine the effect of Blogs, Youtube, and Facebook on the basic understanding of Hinduism Teachings for college students of the Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, directly and indirectly through information satisfaction. The uses and effect mass communication theory was used to support the discussion in this study, which is a synthesis of the uses and gratifications theory and the traditional theory of effects. The population used in this study was 318 students and the sample used was 80 students. The data collection techniques were carried out by questionnaires and observations. The data analysis method used in this study is path analysis using SPSS program. The results showed that youtube and facebook effect the basic understanding of Hinduism teachings directly and indirectly through information satisfaction. While blogs do not affect the basic understanding of Hinduism teachings directly and indirectly through information satisfaction. The value of the total determination coefficient (R-square) obtained from this study is 0.951. This means that Blogs, Youtube, and Facebook effect on the basic understanding of Hinduism teachings by 95.1%, while the remaining 4.9% is influenced by other variables that is not included in this study